2014
DOI: 10.4067/s0718-58392014000300013
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysical pedotransfer functions for groundwater pollution by nitrate leaching in Central Chile

Abstract: Nitrate leaching (NL) is a major concern in agriculture due to its impact on human health and ecosystems. Solute movement through soil is governed by various hydraulic and physical properties that determine water flow. To study such relationships, a pedotransfer function of groundwater pollution was developed in two alluvial irrigated soils under long-term pig slurry applications. Two basins of central Chile, San Pedro (Typic Xerochrepts) and Pichidegua (Mollic Xerofluvents) were selected, where maize (Zea may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recently, in Mediterranean zones of Chile there are further concerns because N and P over-fertilisation in irrigated maize fields can be associated with a high risk of diffuse pollution of water bodies (Casanova et al, 2013;Fuentes et al, 2014;Salazar et al, 2014). This is because in addition to applying high levels of N and P most of farmers utilise a furrow irrigation system with low application al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in Mediterranean zones of Chile there are further concerns because N and P over-fertilisation in irrigated maize fields can be associated with a high risk of diffuse pollution of water bodies (Casanova et al, 2013;Fuentes et al, 2014;Salazar et al, 2014). This is because in addition to applying high levels of N and P most of farmers utilise a furrow irrigation system with low application al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Chile, some recent studies evaluated the impact of agricultural activities on the level of NO 3 -N in water bodies (Fuentes et al 2014(Fuentes et al , 2015Salazar et al 2014). They showed that measured NO 3 -N values in water bodies adjacent to agricultural areas in central Chile, where maize is the most common crop, usually exceed the Chilean water quality standard for drinking water (10 mg NO 3 -N L -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly at the irrigated central Mediterranean of Chile, there are serious risks of diffuse pollution towards surface water bodies and groundwater due to excessive applications of N fertilisers for maize (Zea mays L.) cultivation, predominantly during autumn-winter when bare fallows are practised (Fuentes et al 2014;Salazar et al 2014;Corradini et al 2015;Nájera et al 2015). These concerns also extend to other Mediterranean climate regions of the world (Berenguer et al 2009;Gabriel and Quemada 2011;Salmerón et al 2011;Simeonova et al 2017).…”
Section: Introductionmentioning
confidence: 99%